(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Survey the use of antibiotics in patients with renal failure and evaluate the adjustment of antibiotic doses in patients with renal failure in the Intensive Care Unit, Nghe An General Friendship Hospital. Research methods: A cross-sectional descriptive study was conducted on 55 renal failure patients using antibiotics in the Intensive Care Unit, Nghe An General Friendship Hospital from January 1, 2024 to April 1, 2024. Results: The group aged 60 and above had the highest proportion at 83.6%. Respiratory infections accounted for 79.9%. The average creatinine of the study sample was 263.27 ± 173.62 µmol/L, and the average white blood cell count was 14.20 ± 5.76 G/L. Bacterial culture yielded positive results in 16.4%; in the bacterial identification patterns, Acinetobacter baumanii bacteria are the most prevalent type (55.6%). The rates of combined and single antibiotic use are 58.2% and 41.8% respectively. Betalactam and Quinolone are the two most commonly used antibiotic groups, with the Betalactam and Quinolone combination being the most frequently used. 78.2% of patients with renal failure in the study sample received appropriate dose adjustment. 7/13 antibiotics were 100% consistent. The average duration of antibiotic use is 6.05 ± 2.09 days. Conclusion: Patients with renal failure admitted to the intensive care unit are mostly elderly, with a high rate of respiratory infections. Antibiotics are used in all patients in the study sample. Adjusting the antibiotic dose in renal failure patients is completely reasonable and necessary.